Investigation of mechanisms involved in regulation of progesterone catabolism using an overfed versus underfed ewe–lamb model - Mattos, F. C.S.Z. [UNESP]; Canavessi, A. M.O.; Wiltban, M. C.; Bastos, M. R. [UNESP]; Lemes, A. P.; Mourã, G. B.; Susin, I.; Coutinho, L. L.; Sartori, R. [UNESP] (Oxford University Press (OUP), 2017)
Alterations in progesterone (P4) catabolism due to high feed intake underlie some effects of nutrition on reproduction. Based on previous research, we hypothesized that high feed intake could potentially increase P4 catabolism, likely due to increased liver blood flow. However, there could also be an opposing action due to increased circulating insulin, which has been shown to inhibit hepatic expression of key enzymes involved in P4 catabolism. To test which effect would have the greatest impact on circulating P4 during a 1- and 2 -mo time frame, we used a noncyclic ewe model. The plane of nutrition was controlled, and effects on circulating insulin, P4 catabolism in response to exogenous P4, and steady state mRNA for key hepatic enzymes were evaluated. Twentyfour F1 Dorper × Santa Inês ewe lambs (5 mo old and approximately 25 kg BW) were used. After 14 d of adaptation, ewes were randomized into 2 groups: ad libitum fed (Ad), with intake of 3.8% DM/kg BW, or restricted feed intake (R), with 2% DM/kg BW, for 8 wk. At wk 4 and 8, ewes received an intravaginal P4 implant to evaluate P4 catabolism. As designed, Ad ewes had greater daily feed intake than R ewes (means of 1.8 [SE 0.03] and 0.6 kg/ewe [SE 0.01]; P < 0.001) and greater weekly gain in BW (means of 1.7 [SE 0.12] vs. −0.1 kg/ewe [SE 0.03]; P < 0.001). Mean circulating insulin of samples collected from −0.5 to 7 h after the start of feeding was over 5-fold greater in Ad ewes than in R ewes (least squares means of 8.2 [SE 0.93] vs. 1.5 μIU/mL [SE 0.16], respectively, at wk 4 and 12.0 [SE 1.02] vs. 2.2 μIU/mL [SE 0.18], respectively, at wk 8; P < 0.001). Although both groups received the same P4 treatment, mean circulating P4 of samples collected from −0.5 to 7 h after feeding was much lower in Ad ewes than in R ewes (least squares means of 3.2 [SE 0.32] vs. 5.5 ng/mL [SE 0.32], respectively, at wk 4 and 2.8 [SE 0.28] vs. 5.2 ng/mL [SE 0.28], respectively, at wk 8; P < 0.001) indicating much greater P4 catabolism in ewes with high feed intake. Unexpectedly, there was no effect of diet on hepatic mRNA concentrations for CYP2C, CYP3A, AKR1C, or AKR1D at wk 4 or 8 in spite of dramatically elevated insulin. Therefore, high energy/ feed intake primarily increased P4 catabolism with no evidence for offsetting effects due to insulin-induced changes in hepatic P4 metabolizing enzymes.
Keywords: Hepatic gene expression; Metabolism; Nutrition; Progesterone